PT-symmetric pseudo-perturbation recipe - Mustafa, O; Znojil, M (Iop Publishing Ltd, 2002)
The pseudo-perturbative shifted-l expansion technique (PSLET) is shown to be applicable in the non-Hermitian PT-symmetric context. The construction of bound states for several PT-symmetric potentials is presented, with special attention paid to V(r) = ir(3) - alpharootir oscillators.
Keywords: Shifted 1/N Expansion; Large-N-Expansion; Truncated Coulomb Potentials; Hermitian Quantum-Mechanics; Klein-Gordon Equation; Bound-States; Anharmonic-Oscillators; Schrodinger-Equation; Harmonic-Oscillators; Energy Eigenvalues